Efeito da cafeína sobre a consolidação tardia da memória de medo em ratos - Jesse, Ana Claudia (2016)
Caffeine, an antagonist of adenosine receptors, is one of the most widely consumed psychostimulant substance in the world. There are contradicting reports about the effect of caffeine on learning and memory. While some studies suggest an improving effect of caffeine administration in animal and human models, other reports that caffeine do not affect memory or even impairs. In the present study, we investigated whether caffeine administration alters late memory consolidation and fear memory persistence in contextual conditioning task in rats. Male adult Wistar rats received three 1 s - 0.6 mA footshocks (40 s apart) in a fear conditioning chamber and were injected with saline (0.9 % NaCl, i.p.) or caffeine (0.3, 3 or 30 mg/kg, i.p.) or spermidine (10 mg/kg, i.p.), 12 hours post-training. The testing session was held at 2, 7 or 14 days post-training and the percent of freezing responses was measured. Caffeine administration (3 mg/kg, i.p.) 12 h post-training increased freezing to context of rats tested 2 days after training. Other dose of caffeine were not able to alter freezing to context in the testing session at 7 and 14 days after training. Spermidine administration (10 mg/kg, i.p.) 12 h post-training was able to increase the freezing to context in the testing session carried 2 and 7 days after training. Our findings suggest that late caffeine administration facilitates memory consolidation but not memory persistence in rats.